Influencia de los Stakeholders en la innovación organizacional en empresas michoacanas - Esparza Rodríguez, Saúl Alfonso (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
The present work focuses into inquire into the impact that interest groups such as employees, managers, clients, suppliers, competitors, credit institutions and government have in the innovation in organization management of companies stablished on Michoacan, due to development to innovative activities that conduct to the introduction to new organizational methods such as entrepreneurial practices, organization of the workplace, and external relationships of the company, in those cities that present the higher number of economic units formally stablished in the state, considering Morelia, Uruapan, Zamora and Lazaro Cardenas (INEGI, 2014c), considering as a base a probabilistic cluster sampling in sector such as industrial, commercial and services. The theoretical framework was built under a conceptual framework, scientific theoretical basis and referential framework of innovation, organizational innovation and constructs relatives to managers, employees, customers, suppliers, competitors, credit institutions and governments considered as relevant stakeholders in organizational innovation. The proposed methodology considers analysis of the data recollected via survey in companies stablished in four cities of Michoacan, using correlation coefficient of Spearman, factor analysis and structural equation modeling for hypothesis testing. The results present a contextually located, theoretically sustained and statistically validated model that show the positive, significative and direct influence of employees, competitors, suppliers and clients in the organizational innovation that managers perform in their respective companies, as well as a positive, significative and indirect interaction of customers and suppliers in this form of innovation.

El presente trabajo se enfoca en indagar acerca del criterio de administradores, gestores o gerentes sobre el impacto que grupos de interés tales como empleados, clientes, proveedores, competidores instituciones de crédito y gobierno tienen en la innovación organizacional en empresas michoacanas, en aquellas ciudades que presentan el mayor número de unidades económicas formalmente establecidas en Michoacán, como son Lázaro Cárdenas, Morelia, Uruapan y Zamora, considerando como base una muestra por conglomerados en racimos en empresas de la industria manufacturera. El marco teórico fue construido considerando el marco conceptual, las bases teórico científicas y el marco referencial de la innovación, la innovación organizacional y los constructos relativos a los administradores, empleados, clientes, proveedores, competidores, instituciones de crédito y gobiernos, considerados como grupos de interés relevantes para la innovación organizacional. La metodología considerada para este trabajo se basa en la utilización de un instrumento de recolección de datos con escala de tipo Likert, un análisis de la información recolectada mediante el coeficiente de correlación de Spearman, análisis factorial y utilización de modelos de ecuaciones estructurales (SEM) para el contraste de hipótesis. Los resultados presentan un modelo contextualmente ubicado, teóricamente sustentado y estadísticamente validado que muestra la influencia positiva, significativa y directa de los empleados, competidores, proveedores y clientes en la innovación organizacional que realizan los administradores en sus respectivas empresas, así como una interacción positiva, significativa e indirecta de los clientes y proveedores en esta forma de innovación.
Facultad de Contaduría y Ciencias Administrativas. Doctorado en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-D-2021-1271; Manufactura; Pymes; Gestión organizacional; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6275